Impact of Capnoperitoneum on Renal Perfusion and Urine Production in Infant and Adolescent Pigs: Crystalloid versus Colloid Fluid Resuscitation - Schukfeh, Nagoud; Huber, Dirk; Metzelder, Martin L.; Vieten, Gertrud; Keil, Oliver; Dennhardt, Nils; Suempelmann, Robert; Ure, Benno M.; Kuebler, Joachim F. (European Journal of Pediatric Surgery, 2019)
Background Infants are likely to develop anuria during laparoscopy which is uncommon in older patients. The reason for this susceptibility remains unknown. We compared the impact of CO2 pneumoperitoneum on renal perfusion and urine production in piglets compared with adolescent pigs. We furthermore investigated the effects of different resuscitation strategies.Materials and Methods Male piglets (n = 21) were divided into four groups: (a) infant controls (n = 5), (b) infants with crystalloid restitution (n = 6), (c) infants with colloidal restitution (n = 5), and (d) adolescents with crystalloid restitution (n = 5). Animals were ventilated, the central vessels and ureters were cannulated, and the animals were subjected to a 3-hour, 10 mm Hg CO2 pneumoperitoneum followed by 2-hour resuscitation. Renal perfusion was assessed by fluorescent microspheres and the rate of urine flow was measured.Results Urine production significantly decreased after insufflation only in the infant crystalloid and adolescent group, but not in controls or infants treated with colloids. In the infant crystalloid group, urine production remained at levels below 20% of baseline throughout the experiment. In this group, the renal perfusion dropped significantly after the beginning of the capnoperitoneum and remained significantly reduced throughout the experiment.Conclusion Our data indicates that capnoperitoneum impairs renal perfusion and urine production in infants. In moderate-pressure capnoperitoneum, this effect cannot be compensated by application of crystalloids but with colloids.
Keywords: neonatal; pneumoperitoneum; renal perfusion; laparoscopy; hepatorenal reflex